Design and Application of On-board Computing and Display Control Unit for Mine - CHEN Xiaoxuan; HU Yunqing; ZHANG Guangqiang; LI Xionghui; JIANG Xuezhai; WU Jichang; ZHANG Qiang (Kongzhi Yu Xinxi Jishu)
In the field of open-pit mines, the demand for cooperative operation of auxiliary operation manned vehicles matching intelligent driving mining trucks has become a new industry hotspot. There are many types of auxiliary operation manned vehicle, and the scene of cooperative operation is also complex and diverse, which make cooperative operation very difficult. This paper studies the core components of the collaborative work management system, and puts forward a design method of the on-board computing display control unit that integrates the on-board computing control function and human-computer interaction processing function. This method adopts the modular design method to design the system architecture, system software and hardware architecture and application software architecture of the on-board computer display control unit. According to the characteristics of collaborative work applications, three typical application software interface automatic adaptation schemes are proposed by using the human-computer interaction design method. This method adopts the scheme of covering all cooperative auxiliary operation vehicles with the same set of software and hardware, which can reduce the cost of development and maintenance, and has a good engineering application prospect. The on-board computing display control unit designed according to this method has been applied in an open-pit coal mine, and has realized the loading of various types of vehicles. During the application process, all the cooperative vehicles assist the whole process operation of the unmanned mine trucks as a whole, with smooth cooperation and stable equipment operation.